Institutional Framework and Poverty: A Transition Economy Perspective - Syed M. Ahsan (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper focuses on the role of institutions in poverty alleviation, where both poverty and institutions are interpreted broadly. The broadening of the poverty notion is important at least from the policy perspective. Even if one were convinced that higher growth would reduce income poverty to an acceptable margin, there appears to be little concrete policy measures that one may offer so as to harness greater growth. Besides, the weight of the empirical evidence to date, if not squarely founded on the transition economies of the EEFSU region, is that reducing average poverty is not enough. Existing and possibly rising inequality would ensure that a great many would fall through the cracks, and not benefit from high growth, even if that was achievable. The non-income elements of poverty, on the other hand, are more directly open to influence by policy interventions such as the easing of micro credit and other public and private ventures in health, sanitation, literacy and numeracy fronts. Finally the modest amount of information available at our disposal indicates that the underlying strength of the institutions (economic, political and social) is possibly the single most agent of significance to bring about the alleviation of non-income poverty. There is a further possibility that the same institutional forces would also materially affect the income measure of poverty as well in a discernible fashion.
Keywords: 330